Characterization of Catechol-1,2-Dioxygenase (Acdo1p) From Blastobotrys raffinosifermentans and Investigation of Its Role in the Catabolism of Aromatic Compounds - Meier, Anna; Worch, Sebastian; Hartmann, Anja; Marzec, Marek; Mock, Hans-Peter; Bode, Rüdiger; Kunze, Gotthard; Matthes, Falko (Frontiers in Microbiology, 2022)
Gallic acid, protocatechuic acid, catechol, and pyrogallol are only a few examples of industrially relevant aromatics. Today much attention is paid to the development of new microbial factories for the environmentally friendly biosynthesis of industrially relevant chemicals with renewable resources or organic pollutants as the starting material. The non–conventional yeast, Blastobotrys raffinosifermentans, possesses attractive properties for industrial bio-production processes such as thermo- and osmotolerance. An additional advantage is its broad substrate spectrum, with tannins at the forefront. The present study is dedicated to the characterization of catechol-1,2-dioxygenase (Acdo1p) and the analysis of its function in B. raffinosifermentans tannic acid catabolism. Acdo1p is a dimeric protein with higher affinity for catechol (KM = 0.004 ± 0.001 mM, kcat = 15.6 ± 0.4 s−1) than to pyrogallol (KM = 0.1 ± 0.02 mM, kcat = 10.6 ± 0.4 s−1). It is an intradiol dioxygenase and its reaction product with catechol as the substrate is cis-cis-muconic acid. B. raffinosifermentans G1212/YIC102-AYNI1-ACDO1-6H, which expresses the ACDO1 gene under the control of the strong nitrate-inducible AYNI1 promoter, achieved a maximum catechol-1,2-dioxygenase activity of 280.6 U/L and 26.9 U/g of dry cell weight in yeast grown in minimal medium with nitrate as the nitrogen source and 1.5 % glucose as the carbon source. In the same medium with glucose as the carbon source, catechol-1,2-dioxygenase activity was not detected for the control strain G1212/YIC102 with ACDO1 expression under the regulation of its respective endogenous promoter. Gene expression analysis showed that ACDO1 is induced by gallic acid and protocatechuic acid. In contrast to the wild-type strain, the B. raffinosifermentans strain with a deletion of the ACDO1 gene was unable to grow on medium supplemented with gallic acid or protocatechuic acid as the sole carbon source. In summary, we propose that due to its substrate specificity, its thermal stability, and its ability to undergo long-term storage without significant loss of activity, B. raffinosifermentans catechol-1,2-dioxygenase (Acdo1p) is a promising enzyme candidate for industrial applications.